DevelopmentofMotifs: Designing the Barapan KeboMotif in Kre Alang - Deni, Gustu Rahma; Abdurrozaq, Abdurrozaq (Gorga : Jurnal Seni Rupa, 2024)
The development of the Kre Alang motif (traditional Sumbawa Songket woven cloth) is currently limited to changing the shape and positioning of the motif, which is not very different from the existing motif. This makes the Kre Alang motif less developed and causes boredom among the artisans and consumers of this woven fabric. The objective of this research is to create Kre Alang woven motifs with ideas from one of the traditional games of the Sumbawa people, namely Barapan Kebo (buffalo race). This research employs a textile craft creation method, starting from the exploration stage, followed by design, and then embodiment. Research data was collected through observation, literature review, and interviews. The results of the research are two Barapan Kebo motif designs on Kre Alang woven cloth by incorporating several parts of the Barapan Kebo game which will be used as the main motif on Kre Alang woven cloth, including the buffalo head, joki, and kareng. In addition, Lasuji's motif is used as a supporting motif.